Attitude Towards Tele-Medicine Among Caregivers of Pediatric Patients: Tele-Medicine Among Pediatric Patients - Rizwan, Shazia; Qamar, Sobia; Rehman, Rabeya; Shahalam, Sobia; Iqbal, Madiha; Mushtaq, Ayesha (Pakistan Journal of Health Sciences, 2025)
Telemedicine is a vital constituent of digital health-care, particularly stating the deliverance of medical facilities over remote areas by means of Information and Communication Technologies (ICT). The swift progress of mobile applications has improved support for health-care experts, rationalization responsibilities such as time organization, communication, and policymaking. Objective: To assess attitudes of parents having children aged between one to twelve years towards telemedicine. Methods: The cross-sectional study employed an online survey with the sampling strategy as convenience method for recruitment of eligible parents. A self-administered questionnaire was employed to gather sociodemographic data, child-related information, and participants’ technological profiles. Attitudes toward telemedicine were measured using a 5-point scale, evaluating the perceived usefulness of various telemedicine services and associated advantages. Data analysis included descriptive statistics to summarize sociodemographic variables and item prevalence, while excluding any missing values. Results: A total of 120 families participated in the study, with caregivers averaging 47.4 years in males, 43.1 in females and children 7.5 years old. The majority of caregivers were female (68.3%), and most children were male (53.3%). Technological profiles indicated high smartphone availability (93.3%) and moderate use of social media accounts. Attitudes toward telemedicine showed significant perceived usefulness, particularly for scheduling medical visits (54.1% rated it as moderate/much) and telemonitoring services (49.1%). Participants recognized advantages of telemedicine, highlighting time efficiency (44.1%) and financial savings (46.6%) as key benefits. Conclusion: Families of pediatric patients demonstrated a strong willingness to engage in telemedicine programs. They showed positive attitude towards usefulness of telemedicine.